Bermudagrass Production in Florida - Carrol G. Chambliss; Freddie A. Johnson (EDIS)
The improved hybrid bermudagrasses (Cynodon dactylon L.) are used for both hay and grazing. Coastal was the first hybrid bermudagrass developed at the Coastal Plain Experiment Station in Tifton, Georgia, and was released in 1943. Several other bermudagrass varieties have been developed since then by both public agencies and private individuals. Hybrid bermudagrasses have been popular for hay production because they are very responsive to nitrogen fertilizer, have high yield potential, and usually dry or cure faster than most other forages that could be used for hay. Bermuda makes good use of animal manures and so has been widely used by the poultry and dairy industries. Overseeding of winter forages has generally been more successful on bermudagrasses than on bahiagrasses. Many research studies have shown high animal weight gains per acre when bermuda is well fertilized.